A brain mass in a patient with Behcet's disease: a case report. (December 2015) - Alfedaghi, Ahmad; Masters, Y.; Mourou, M.; Eshak, O.
Abstract Introduction This case report describes an uncommon presentation of Behcet's disease which manifested as neuro-Behcet's disease. Although it is not the first reported case in the medical literature, it is a possible differential in a patient presenting with a brain tumor. Since the diagnosis of neuro-Behcet's disease depends largely on the clinical picture and medical history, it should be considered prior to opting for invasive diagnostic methods. Case presentation Our patient is a 36-year-old white man from Kuwait. He presented with acute onset of headache, vomiting, and right-sided weakness. Magnetic resonance imaging of his brain showed a mass in the brain stem. He then revealed that he had a history of recurrent painful oral and genital ulcers for the past 10 years, which suggested a diagnosis of Behcet's disease. A brain biopsy was recommended by a neurosurgeon at the time, but the patient refused the procedure. After initiating steroid therapy, the mass began to regress and, eventually, was undetectable on subsequent imaging of his brain. Conclusions This case of neuro-Behcet's disease reflects the need to consider this diagnosis in a patient of less than 40 years of age presenting with a suspected brain tumor. This may delay the need for invasive diagnostic methods, especially if such methods are not desired by the patient. In the management of suspected neuro-Behcet's disease, initiating steroid therapy and measuring the response is a reasonable option before seeking a definitive diagnosis via brain biopsy. If the response to steroids is minimal then a brain biopsy should be performed.